Development of Bread Dough by Sheeting: Effects of Sheeting Regime, Bran Level and Bran Particle Size - Mohamed Otman Saleh Albasir; Mohammad Alyassin; Grant Murray Campbell (Foods, 2022)
The effects of sheeting on bread dough development and baked loaf quality were investigated, using Dynamic Dough Density and springback to quantify development, and examining effects of the sheeting regime on bread quality in terms of loaf volume and crumb structure. Bread doughs, with and without bran at different levels and particle sizes, were formed through a short mixing period, then sheeted through a benchtop manual sheeter at roll gaps of 6, 9 and 12 mm for different numbers of sheeting passes. The sheeting of doughs without bran increased dough expansion and baked loaf volume up to 12 sheeting passes. Loaves were larger after sheeting at a 6 mm roll gap, reflecting the greater gluten development at the smaller gap, although the crumb structure was less fine, with fewer gas cells and larger average gas cell diameters. The addition of bran decreased dough expansion and loaf volumes, with Fine bran and Coarse bran both more damaging than Medium bran, indicating the opportunity to optimise bran particle size to maximise bread quality. Sheeting was effective in alleviating the damaging effects of bran, with sheeting for 8 passes giving more dough expansion, larger loaf volumes and finer crumb structures than sheeting for 12 passes, indicating an even more damaging effect of bran when gluten is overstretched by sheeting. The work demonstrates the opportunity to enhance bread quality, particularly of healthy high-fibre breads, by employing sheeting to enhance gluten development and to offset the damage to gluten caused by the presence of bran.